2018
DOI: 10.3390/jcm7050096
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass, Total Body Fat Percentage, and Visceral Fat Level Predict Insulin Resistance Better Than Waist Circumference and Body Mass Index in Healthy Young Male Adults in Indonesia

Abstract: The incidence of obesity which leads to insulin resistance (IR) and metabolic disorder is increasing in developing countries, including Indonesia. Male adults have a higher risk of abdominal obesity than females. This is associated with cardiometabolic disorders. Several anthropometric measurements have been proposed to predict IR. The aim of this study was to investigate whether body mass, body mass index (BMI), waist circumference (WC), body fat percentage (BF) or visceral fat level (VF) could become a bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 20 publications
(23 reference statements)
2
38
1
5
Order By: Relevance
“…Our results are similar to those of a cross-sectional study by Huang et al (2012) who used regression analysis of 144 individuals with T2DM to show that unlike BMI, WC is a statistically significant predictor of HOMA-IR. Although a cross-sectional study of 140 healthy individuals by Kurniawan et al (2018) found, consistently with the present study, a stronger correlation of HOMA-IR with WC (r=0.46, p<0.01) than with BMI (r=0.39, p<0.01), regression analysis proved BMI to be a stronger predictor of HOMA-IR than WC. with 95 % confidence bands for the medians of variables on the y-axis for a given variable on the x-axis.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those of a cross-sectional study by Huang et al (2012) who used regression analysis of 144 individuals with T2DM to show that unlike BMI, WC is a statistically significant predictor of HOMA-IR. Although a cross-sectional study of 140 healthy individuals by Kurniawan et al (2018) found, consistently with the present study, a stronger correlation of HOMA-IR with WC (r=0.46, p<0.01) than with BMI (r=0.39, p<0.01), regression analysis proved BMI to be a stronger predictor of HOMA-IR than WC. with 95 % confidence bands for the medians of variables on the y-axis for a given variable on the x-axis.…”
Section: Discussionsupporting
confidence: 90%
“…The VFL is a simple method that correlates with the fat mass. [51] In our study, BFM and VFL were not correlated with SUA level in both genders. These findings may suggest that central adiposity markers have closer associations with SUA level than markers of general adiposity.…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, previous studies have reported that sex differences needed to be considered when discussing lipid and lipoprotein metabolism and susceptibility to develop obesity, diabetes and CVD. [27][28][29] We found a higher MetS prevalence in males than females across all three criteria, based on the male to female ratio (1.02) among Chinese adults (aged 18 years and older) in 2010. This corroborated results from previous studies which indicated higher MetS prevalence in males before the age of 50 years and higher in females after the age of 50 years, 30 31 MetS prevalence by different age groups are recommended for future studies.…”
Section: Open Accessmentioning
confidence: 73%